2014
DOI: 10.1213/ane.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Index of Hypoxemia for Assessment of Risk During Procedural Sedation

Abstract: Anesthesiologists determined arterial oxygenation to be the most important physiological variable in assessing sedation risk and the potential for adverse clinical outcomes. AUCDesat, a composite index that incorporates duration, incidence, and depth of oxygen desaturation, was better correlated to the Likert scores. AUCDesat, given that it is a single numerical variable, is an ideal end point for assessment of risk of adverse clinical outcomes in clinical sedation studies. Future studies using AUCDesat and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…For example, if a person's oxygen saturation was 85% for a period of 30 seconds, the AUC Desat 90% for that duration was 150 (seconds %). The AUC Desat combined the incidence, duration, and magnitude of a patient's oxygen desaturation and better reflected the duration and severity of hypoxemia than the lowest saturation or the number of hypoxic events [28, 29].…”
Section: Methodsmentioning
confidence: 99%
“…For example, if a person's oxygen saturation was 85% for a period of 30 seconds, the AUC Desat 90% for that duration was 150 (seconds %). The AUC Desat combined the incidence, duration, and magnitude of a patient's oxygen desaturation and better reflected the duration and severity of hypoxemia than the lowest saturation or the number of hypoxic events [28, 29].…”
Section: Methodsmentioning
confidence: 99%
“…Niklewski et al introduced the use of the AUC of desaturations to integrate the number, depth, and duration of oxygen desaturations. 14 By integrating these factors into one outcome measure, one might better understand the magnitude of desaturation and therefore the potential risk of the associated hypoxemia. Since the clinical importance of hypoxemia is uncertain, we displayed the dimensions of hypoxemia in our population by AUC.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the risk of artifacts possibly resulting from the sampling rate of one value per minute by the AIMS, hypoxemia was defined as oxygen saturation < 90% lasting for two or more consecutive minutes. We calculated the area under the curve (AUC) as previously shown, 14 with a small adaption in time period. For each hypoxemic event, time in minutes, magnitude of oxygen desaturation, and AUC (by multiplying duration in minutes and the drop in saturation under 90%) were determined.…”
Section: Methodsmentioning
confidence: 99%
“…It has been posited that surrogate outcomes must be in the causal pathway of injury with correlation alone not being sufficient [15]. A recent study reported that arterial oxygen saturation is the most important physiological parameter in assessment of risk of adverse outcomes during sedation [16]. For this reason, we determined that reduction in episodes of hypoxaemia would be the most suitable surrogate marker to investigate the potential patient safety benefits that may be associated with using DoA monitors of depth of sedation during PSA.…”
Section: Introductionmentioning
confidence: 99%